1988
DOI: 10.1021/bi00421a029
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic lactam analogs of Ac-[Nle4].alpha.-MSH4-11-NH2

Abstract: Two side-chain cyclic lactam analogues of the 4-11 fragment of alpha-melanocyte-stimulating hormone (alpha-MSH), Ac-[Nle4,D-Orn5,Glu8]alpha-MSH4-11-NH2 and Ac-[Nle4,D-Orn5,D-Phe7,Glu8]alpha-MSH4-11-NH2, were prepared on p-methylbenzhydrylamine resin by using a combination of N alpha-Boc and N alpha-Fmoc synthetic strategies with diphenyl phosphorazidate mediated cyclization. The melanotropin activities of these two analogues were examined and compared relative to those of alpha-MSH, Ac-[Nle4]alpha-MSH4-11-NH2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 13 publications
(15 reference statements)
4
23
0
Order By: Relevance
“…The His 6 imidazole ring formed a roughly T-shaped alignment with the phenyl ring of Phe 7 . The details of this structure are in good agreement with the structure proposed by Hruby and co-workers on the basis of their nmr and structure-function studies, 37 though it has not been reported before in theoretical studies.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…The His 6 imidazole ring formed a roughly T-shaped alignment with the phenyl ring of Phe 7 . The details of this structure are in good agreement with the structure proposed by Hruby and co-workers on the basis of their nmr and structure-function studies, 37 though it has not been reported before in theoretical studies.…”
Section: Introductionsupporting
confidence: 90%
“…This kind of spatial arrangement was proposed to be important to the potency of the hormone 37 and was also observed in the structure determined in our previous study. 66 Another interesting question about the conformation of ␣-MSH is whether the biologically active structure is stabilized by a salt bridge.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…22, 23 The results of energy calculations for ␣-MSH and the c[Cys 4 , Cys 10 ]␣-MSH showed that the Glu 5 and Arg 8 side chains are in close proximity and that a salt bridge between the two side chains may stabilize the biologically active conformation of ␣-MSH. 24,25 In a later study on ␣-MSH and its cyclic analogues, Nikiforovich et al 26 proposed a conformational model for binding and signal transduction, where the side chains of His 6 , L/D-Phe 7 , and Trp 9 residues form a continuous hydrophobic surface and the Arg 8 side chain is oriented away from them.…”
mentioning
confidence: 99%
“…It can induce follicular melanogenesis in some rodents and dogs 11 and has been found to be physiologically stable and long acting in animals. 10,[12][13][14] As with most peptides, the oral bioavailability of melanotan II is low and the drug must be administered as a parenteral, which is impractical for chronic dosing. In order to better accommodate this problem, the systemic delivery of melanotan II through other routes of administration has been investigated.…”
Section: Systemic Delivery Of Melanotan II Through the Ocular Route Imentioning
confidence: 99%